Development of a methodology for systematic analysis of risk reduction by protective measures in tyre production machinery. (December 2018) - Compare, M.; Zio, E.; Moroni, E.; Portinari, G.; Zanini, T.
Highlights: A systematic methodology for risk analysis is presented. The methodology is compliant with ISO 12100. A classification of the protective measures for risk reduction is provided. Reduction scores are calculated relative of the risk factors. The methodology is applied to a curing machine for tyre vulcanization. Abstract: SO/TR 14121-2: 2012 considers three factors to describe the likelihood of the occurrence of an incident scenario: the frequency of exposure of persons to the hazard, the probability of occurrence of the hazardous event and the technical and human possibilities of avoiding harm. The assessment of these factors can be quite controversial, especially when it concerns the amount of risk removable by protective measures: their mapping onto the risk factors is not always clear and this can lead to non-conservative over-estimations of the risk reduction. We propose a methodological framework compliant with ISO 12100 to systemically carry out repeatable risk analyses in support to the design of industrial machinery in which protective measures can be introduced to reduce risk. The methodology first proposes a scheme for identifying the contribution of PMs to the reduction of risk in a machinery under design. Then, the methodology classifies the protective measures and builds a clear mapping between these classes and the risk factors they impact on. This helps decision makers to identify the protective measures guaranteeing that the residual risk is acceptable. The methodology is applied to a real case study concerning a curing machine for tyre vulcanization, where it has proven to be beneficial for the clarity of the analysis and its repeatability.